Barriers to accessing online medical records: an analysis by priority condition status. (15th September 2022) - Mukhopadhyay, Surma; Basak, Ramsankar; Carney, Timothy Jay; Carpenter, Darrell
The objectives were to assess: 1) offering of access to online medical records (OMR) to patients by their providers; 2) the reasons for patients' non-use of OMR. Using Health Information National Trends Survey 5, Cycle 1 and 2 data, the study included 3, 948 adults who had internet-enabled devices and recent provider visits. 39% were not offered access and 1, 612 were non-users, many with ≥ 2 priority conditions (e.g., diabetes, cancer). Demographic attributes were significant predictors of access offering. Of priority condition non-users, 77.6% cited preferring speaking directly, 54.2% no need, 24.3% privacy concerns, and 23.9% lack of any OMR. Reporting of no need was significantly associated with education, race, and number of diseases while speaking directly with residence and anxiety/depression. Many, including those with priority diseases and/or regular sources of care, expressed multiple reasons for non-use displaying interrelationships among reasons. Addressing underlying barriers can help reduce usage disparities and improve outcomes.